Allocation and Sizing of Energy Storage System Considering Wind Uncertainty: An Approach Based on Stochastic SCUC - Habibi, Mahdi; Oshnoei, Arman; Vahidinasab, Vahid; Oshnoei, Soroush (2018 Smart Grid Conference (SGC), 2018)
Nowadays, the upgrading integration of renewable energy resources affords more uncertainties in the planning and operation of power grids particularly the neighboring power grids, which are connected through the tie-lines. As a consequence, the importance of expanding of energy storage systems (ESSs) and efficient allocation and sizing of ESSs in power grids in order to enhance the performance of the power grid under some uncertainty such as wind power uncertainty grandstands more than ever. Accordingly, this paper proposes a model based on stochastic security constrained unit commitment (SCUC) problem to find the optimal location and size of the ESS units. In the proposed model, the ESSs help operators with preventive actions and do not cooperate in wind scenarios. The ownership of ESSs is assumed to be private, and their scheduling is fulfilled subject to the day-ahead market. The violations to the predicted wind power are handled with the deployment of operational reserve and optimal load shedding. The evaluation of the proposed model is performed in different cases on IEEE RTS-96 test system. The results show the effectiveness of the proposed framework in determining the optimal sizes and locations of ESSs and increasing the operation efficiency (reduction of the peak-load and operational costs) by storing the extra wind power.